Perceived Precautionary Savings Motives: Evidence from FinTech - Francesco D'Acunto; Thomas Rauter; Christoph Scheuch; Michael Weber; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2020)
We study the spending response of first-time borrowers to an overdraft facility and elicit their preferences, beliefs, and motives through a FinTech application. Users increase their spending permanently, lower their savings rate, and reallocate spending from non-discretionary to discretionary goods. Interestingly, liquid users react more than others but do not tap into negative deposits. The credit line acts as a form of insurance. These results are not fully consistent with models of financial constraints, buffer stock models, or present-bias preferences. We label this channel perceived precautionary savings motives: Liquid users behave as if they faced strong precautionary savings motives even though no observables, including elicited preferences and beliefs, suggest they should.
Keywords: D14; E21; E51; G21; 330; household finance; consumption; behavioral finance